2019
DOI: 10.1029/2018ja026030
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields of Magnetospheric ULF Disturbances in the Ionosphere: Current/Voltage Dichotomy

Abstract: A circuit analogy for magnetosphere‐ionosphere current systems has two extremes for drivers of ionospheric currents: the “voltage generator” (ionospheric electric fields/voltages are constant, while current varies) and the “current generator” (current is constant, while the electric field varies). Here we indicate another aspect of the magnetosphere‐ionosphere interaction, which should be taken into account when considering the current/voltage dichotomy. We show that nonsteady field‐aligned currents interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Quantitative relationships between conjugate Δ B amplitudes and height‐integrated ionospheric conductances for these two generators were examined by Pilipenko et al (2019) using a simple “plasma box” model of the magnetosphere with asymmetric conjugate ionospheres driven by an external current located at the magnetospheric equatorial plane. The ranges of validity of current and voltage generators are determined by the ratio between an internal generator resistance and a load resistance.…”
Section: Comparison Of Amplitudes In Conjugate Hemispheresmentioning
confidence: 99%
“…Quantitative relationships between conjugate Δ B amplitudes and height‐integrated ionospheric conductances for these two generators were examined by Pilipenko et al (2019) using a simple “plasma box” model of the magnetosphere with asymmetric conjugate ionospheres driven by an external current located at the magnetospheric equatorial plane. The ranges of validity of current and voltage generators are determined by the ratio between an internal generator resistance and a load resistance.…”
Section: Comparison Of Amplitudes In Conjugate Hemispheresmentioning
confidence: 99%
“…The conclusions made here are valid for a short pulse when a conjugate ionosphere does not influence the pulse interaction with the ionosphere of interest. The presented study completes together with Pilipenko et al (2019) the consideration of ULF wave and transient interactions with the ionosphere and its dependence on the ionospheric conductance from the view of the current-voltage dichotomy. At low latitudes, the SC can be considered as driven by a quasi-DC source, and its properties must correspond to the voltage generator regime.…”
Section: Resultsmentioning
confidence: 85%
“…Judging from the seasonal and interhemispheric variations of SCs at low‐latitudes, it may be concluded that the SC in this region is caused by a voltage generator rather than a current generator. Thus, the observed strong dependence on conductance corresponds to the regime of a voltage generator, natural for a nonresonant quasi‐DC disturbance (Pilipenko et al, ).…”
Section: Comparison Of Theoretical Predictions With Results Of Low‐lamentioning
confidence: 95%
See 1 more Smart Citation
“…Quantitative relationships between conjugate ΔB amplitudes and height-integrated ionospheric conductances for these two generators were examined by Pilipenko et al (2019) using a simple "plasma box" model of the magnetosphere with asymmetric conjugate ionospheres driven by an external current located at the magnetospheric equatorial plane.…”
Section: Comparison Of Amplitudes In Conjugate Hemispheresmentioning
confidence: 99%